SPIRIT PEACEBUILDING MELALUI KOMUNITAS PEMUDA DI YOGYAKARTA - BJ Sujibto (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2015)
This research examines the role of youth-based community involved in pence movement on promoting peacebuilding among youths In Yogyakarta and it surrounding. This grassroots Movement as micro-level peacebuilding spectrum ruled by youth faces more challenges in term of students’ brawls and othcr violence in which peer-age youths have taken apart in this cases over last few decades. The escalation -of youth violence represented by students of both from university and senior high school getting involved in bowls has Increased to open the access into public sphere and they have made scared everywhere by pointing ‘hoi zone’ of violence. Peacebuilding process can lake an important role to end youths’ violence by training to attain personal achievement, involving in social activities and addressing a basic peace education so that a “peace” word can be familiar one fid become part of their everyday’s life style with friends in school instead of talking about harm and taking revenge against their enemy from other school. Peacebuilding talkabout reconcilitation how to make peace and live in harmony among the people by understanding indigenous capacities which don’t merely focus on conflct resolution hut it takes time into sustainable peace process. Youth community/ which concerns on peace movement is the answer for eradicating youth’ potential violence in near future. It accomodates widely-opened places, bridging dialog, inviting more and more young generations to meet and talk each other, understanding identities and respecting difference among them. Peace generations represents a community which is active in conflct resolution and peace within youth society. In has involved and initiated many youth activities concerning in peacebuilding process by promoting its core’ values such as youth, participations, pluralism, and active non-violence as the essential basic of its movement. In doing so, youth in the community must be frontrunner for peace to make possibility of achieving a real long-term gain of peace cultures and peace patterns, counting for the peaceful means to practice. Youth initiatives, however, to peacebuilding among their peer are exactly needed in process of sustainable peace by intriguing indigenous capacities as main preference to make patterns of peace culture